(untitled) (Indian Journal of Dairy Science, 2023)
The triglyceride profiling of ghee shows significant variations in different regions of India, influenced by factors such as feeding practices, fatty acid composition, lactation stage, and season. Our study focused on detecting and identifying ghee adulterated with cottonseed oil and ghee sourced from the cotton tract area. Triglyceride profiling was employed on pure, adulterated, and cotton tract area ghee samples. Our findings revealed consistent lower levels of triglycerides with carbon numbers C24 to C30 in cow ghee, while higher levels were observed for carbon numbers C38 to C40 and C50 to C54. However, in ghee adulterated with cottonseed oil, triglycerides with carbon numbers C34 to C38 significantly increased (p<0.05), while those with carbon numbers C50 to C52 decreased significantly (p<0.05) with increasing concentrations of cottonseed oil. To verify the authenticity of the ghee samples, we analyzed normal cow ghee from LRC, NDRI using parameters including S-total, S2, S3, S4, and S5. The observed values for these parameters (98.77 ± 0.23, 103.30 ± 0.19, 99.55 ± 0.22, 97.42 ± 1.31, and 98.34 ± 0.27, respectively) fell within the ISO standard range. In conclusion, our study highlights the potential of triglyceride profiling as an effective tool for detecting and differentiating ghee adulterated with cottonseed oil and ghee sourced from the cotton tract area. The method is suitable for detecting the presence of cottonseed oil at a lower level of 10% in ghee. This technique provides valuable insights into assessing the authenticity and quality of ghee, contributing to the prevention of adulteration practices in the ghee industry.